Ragnar Loðbrók Isn’t Real: The Limits of Treating Sagas Like History - Bierstedt, Adam (Mittelalter Digital, 2021)
Ragnarr Loðbrók is perhaps the most famous Viking in modern consciousness. Between History Channel’s ›Vikings‹ and ›Assassin’s Creed: Valhalla‹, this 9th century Scandinavian king dominates the image of an egalitarian society, where a farmer can, through his own brilliance, perform famous deeds and becomes a renowned, conquering king, whose death causes his sons and loyal drengir to invade and conquer most of England in the Great Viking Army.